Comparison between infants receiving traditional supplements (camel thorn, flix weed, and sugar water) and exclusively breast fed infants - Hassan Boskabadi; Sepideh Bagheri (Mashhad University of Medical Sciences, 2015)
Objectives: Although breast milk is considered the best nutritional option for neonates, use of traditional supplements such as sugar water, camel thorn, and flix weed in the first week of life of infants is quite common in Iran and many other countries. The aim of this study was to evaluate whether consuming such supplements has any impact on infant's breastfeeding behavior. Materials and Methods: Four hundred fifty four term infants who were referred to the neonatal clinic of Ghaem hospital were enrolled and divided into two groups. Control (exclusively breastfed infants, N=243) and case (breast milk feeding plus traditional remedies such as sugar water, camel thorn, and flix weed, N=211). Spss 19.5 was used for statistical analysis. T-test and Man-Whitney tests were used. A p-value of Results: The two groups were similar in their baseline data. Regarding duration of breastfeeding and breastfeeding frequency, use of these supplements resulted in a reduction in both breastfeeding frequency and duration (p